2021
DOI: 10.3390/su13073793
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Cost Effects of Plot-Level Wheat Seed Rates and Seed Recycling Practices in the East Gojam Zone, Amhara Region, Ethiopia: Application of the Dose–Response Model

Abstract: Previous studies investigated the effects of seed rates and seed recycling practices on the yield and yield-related variables. However, higher yield does not always guarantee cost-efficiency. This study aimed to investigate the yield effects of plot-level seed rate and the cost–benefit analysis of seed recycling practices. This study has introduced the dose–response model to the existing analytical methods used in analyzing the effect of different agrochemicals on crop yield. A multi-stage stratified sampling … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(29 reference statements)
1
1
0
Order By: Relevance
“…Consequently, their IPCC-LVI is closer to zero (0.09), which is significantly lower than that of non-adopters (0.12) (p < 0.01), which shows that adopters are significantly less vulnerable to climate change than non-adopters. Hence, the adoption of improved varieties significantly enhances adaptation to climate change, which concurs with studies [37,72,74], which reported that improved varieties enhance climate resilience and food security through the adop-tion of high-yield, improved wheat varieties and drought-resistant maize varieties among smallholder farmers.…”
Section: Livelihood Vulnerability and Adoption Of Csa Innovationssupporting
confidence: 87%
“…Consequently, their IPCC-LVI is closer to zero (0.09), which is significantly lower than that of non-adopters (0.12) (p < 0.01), which shows that adopters are significantly less vulnerable to climate change than non-adopters. Hence, the adoption of improved varieties significantly enhances adaptation to climate change, which concurs with studies [37,72,74], which reported that improved varieties enhance climate resilience and food security through the adop-tion of high-yield, improved wheat varieties and drought-resistant maize varieties among smallholder farmers.…”
Section: Livelihood Vulnerability and Adoption Of Csa Innovationssupporting
confidence: 87%
“…Additionally, the zone is vulnerable to problems induced by climate change, such as land degradation, recurrent drought, parasitic weeds, disease, and insect pests [ 27 ]. Three districts (Debre Elias, Gozamin, and Basoliben) in the east Gojjam zone were chosen purposively due to the presence of high wheat production areas and vulnerable to problems induced by climate change [ 52 , 53 ]. Then, in the first stage, seven kebeles were randomly selected in proportion to the number of Kebeles in each district.…”
Section: Methodsmentioning
confidence: 99%